Synchronicity : the inner path of leadership - Jaworski, Joseph, 1934- (BK business book., 2011)
We?ve all had those perfect moments when events that could never be predicted, let alone controlled, remarkably seem to guide us along our path. Carl Jung called this phenomena?synchronicity???a collaboration between persons and events that seems to enlist the cooperation of fate.? In this book, Joseph Jaworski argues that the right state of mind will make you the kind of person who can enlist the cooperation of fate and take advantage of synchronicity, creating the conditions for?predictable miracles.? If you are tired of being the victim of circumstances, this book will teach you to be the kind of person who creates your own circumstances. Jaworski shares the story of his own escape from an inauthentic life and his journey into a world filled with possibility. He maps out the inner path of leadership for those who feel the call to achieve their full potential, using his own life story to teach readers a greater truth. He examines the fundamental shifts of mind that free us to seek out the power of synchronicity. After reading this book, you will discover your own power to help those realities unfold. You will learn to?listen? to realities that want to emerge in this world and acquire the courage to help them be born. Synchronicity illustrates that leadership is about the release of human possibilities, about enabling others to break free of limits? created organizationally or self-imposed. Although this book describes the author's personal journey, it contains profound messages about organizational learning and effectiveness.? Scientific American.